Impact of Cement Dust on Soil Composition Near ElFataih Cement Factory: An X-Ray Fluorescence–Based Study - Reema Abdullah; Sajidah Aljamie; Areg Nasser; Montaha Alturkawi (AlQalam Journal of Medical and Applied Sciences, 2025)
The X-Ray Fluorescence (XRF) technique was utilized to examine how the cement dust from Elfataih influences soil pH and to assess the concentrations of metal oxides in both the surface and subsurface soil samples collected from the areas surrounding the El-Alfataih region. The findings from this research revealed a direct impact of the cement dust on the distribution of metal oxides in the analyzed soil samples, highlighting a variation between the oxides present in the surface and subsurface layers. Different types of metal oxides were detected in the studied samples, including CaO, SiO2, Al2O3, Fe2O3, Na2O, MgCO3, K2O, MgO, SO3, TiO2, P2O5, and MnO, besides the presence of different amounts of calcium carbonate, CaCO3, and Magnesium carbonate, MgCO3. The results of PH values showed high variations, their values ranged between (7.8± 0.05 and 8.8±0.01) for the subsurface samples, compared with the values of surface samples of (7.28 ± 0.01 and 9.48 ±0.1). In general, elevated levels of metal oxides were observed in the surface samples in comparison to the subsurface ones. Moreover, the results indicated that certain areas exhibited higher concentrations than others, with the most significant values noted in the southern and eastern parts near the factory locations.